The Impact of Nutritional School Based Feeding Program on Academic Achievement of Selected Elementary Learners in West Philippines - Alcantara, Maryjane A.; Marisa A. Frontreras (Yayasan Nurul Yakin Bunga Tanjung, 2024)
This study investigates the impact of nutritional school-based feeding programs on the academic performance of 45 elementary learners. This research method uses a quasi-experimental design with a pretest and posttest structure; a two-part questionnaire was the primary research tool. The first part gathered demographic information, while the second assessed participating students’ nutritional status and academic performance. Researchers administered the questionnaire to parents or caregivers, selected students systematically, traced household addresses, and conducted home interviews. The study results showed that the general weighted average increased noticeably and statistically significantly after implementing school-based feeding programs. Subsequent investigation, however, revealed a fascinating finding: the gains in academic achievement did not correspond consistently with the varied profiles of respondents, including age, gender, socioeconomic status, and educational attainment. The research highlights the necessity for additional investigation into the impact of nutrition on academic achievement.